Arboreal Toponyms: tree place-names in early medieval England - Treacher, Jessica (2023)
This thesis provides a comprehensive overview of early medieval major settlement names in England that have a tree-species element. By examining how tree-names appear in place-names and how they are compounded with habitative and topographical terms, this work contributes to our knowledge of the development of tree words in English and is an aid to better understanding the early medieval arboreal landscape. It demonstrates where species were dominant and how they might have been perceived and used as resources by early medieval communities. The introductory discussion looks at past scholarship on tree toponyms and considers what a tree was thought be in the cultural mindset of early medieval England: suggesting that medieval perceptions were more flexible than those imposed by modern taxonomy. The corpus analysis groups toponyms alphabetically by tree-species element and begins by discussing the phonological development of each tree word, this is then followed by an in-depth consideration of how these words compound in place-names. Interesting patterns in tree-name distribution suggest that tree-species were valued differently for their unique properties and characteristics. Some species were favoured as landmarks and locations where gatherings of civic and religious importance were held; some appear to have been used for the demarcation of land and as a means of corralling livestock; and others were a favoured source of timber or provided food for human or animal consumption. Where native tree-species do not appear in place-names, this can likely be attributed to their lack of accessibility or usefulness. There are three case-studies that focus on the use of trees as consumable resources. The first considers place-name evidence for timber-producing sites, while the second examines probable orchard names. Recurrent tree-names with a tūn or bȳ generic were likely to have been settlements that were established for the purpose of managing trees and woodland to produce timber, coppice, and fruit. These sites appear often to have been parts of larger estates or were connected to centres of commerce where produce could be sold. Their distribution would have been primarily influenced by the availability of suitable tree-species, although the cultivation of domesticated varieties is also likely to have occurred at orchard sites. The third case-study looks at ‘nut’ place-names, particularly those with a hnutu element. Names in hnutu seem not to have referred to a particular species but instead to locations where a nut harvest was abundant, palatable, or notable within the wider landscape. In individual cases this word may also have been used in the vernacular to refer to an unfamiliar nut-bearing species.